Effect of sow diets supplementation with chelated trace minerals on their reproductive performance - SKAMPARDONIS (Β. ΣΚΑΜΠΑΡΔΩΝΗΣ) V.; LISGARA (Μ. ΛΙΣΓΑΡΑ) M.; PAPATSIROS (Β. ΠΑΠΑΤΣΙΡΟΣ) V.; LEONTIDES (Λ. ΛΕΟΝΤΙΔΗΣ) L. (Journal of the Hellenic Veterinary Medical Society, 2018)
Trace minerals are constituents of proteins and enzymes that are involved in a variety of metabolic processes, having functional implications in growth, development, reproduction and health. Chelated minerals, are minerals bound to organic ligands, usually amino acids, providing higher levels of bioavailability compared to conventional inorganic mineral sources. In the present study, we investigated the effect of partial substitution of inorganic mineral sources with chelated minerals in sows’ diets, on three important reproductive parameters, the number of liveborn and weaned piglets and the wean-to-first service interval, in three Greek farrow-to-finish herds. Before initiation of the study the sows were on diets supplemented with 15 mg/kg feed Cu (from CuSO4), 125 mg/kg Zn (from ZnO) and 40 mg/kg Mn (from MnO). After exiting the farrowing facilities they were offered diets in which 93.3%, 36.0% and 62.5% of the supplemented Cu, Zn and Mn, respectively, originated from commercially available chelated minerals. For the last farrowing on inorganic minerals diet and the subsequent one or two (for 35.0% and 65.0% of the studied sows, respectively) on chelated minerals, each sow’s reproductive data (total number of parities, number of liveborn and weaned piglets and wean-to-first service interval) were recorded. The reproductive parameters, before and after the supplementation with chelated minerals, were compared in two mixed-effect linear regression models, for the number of liveborn and weaned piglets, and in a zero inflated negative binomial model for the weaning-to-first service interval. There was an improvement of the mean number of liveborn piglets after partial substitution of inorganic source of minerals with chelated minerals by almost half a piglet (P=0.015), whereas there was no effect on the total number of weaned piglets (P=0.15) and the wean-to-first service interval (P=0.65). The increase in the number of liveborn piglets may be directly attributed to improved embryo survival due to increased bioavailability of the organic minerals or indirectly to the beneficial effect of chelated minerals on sows’ hoof health, locomotor ability, feed intake and body condition.